Scandal in Japan: transgression, performance and ritual - Prusa, Igor (Japan anthropology workshop series, 2024)
"This book is an exploration of media scandals in contemporary Japanese society. Shedding new light on the study of scandal in Japan, the book offers a novel view of scandal as a specific social ritual which follows moral disturbances in Japanese society. Society and culture are analyzed largely in terms of social performances, while the focus is on how Japanese transgressors talk and act when explaining their scandals to the public. A detailed analysis of three case studies is provided: the drug scandal of the popular Japanese celebrity Sakai Noriko from 2009, the political donation scandal from 2009 centering the heavyweight politician Ozawa Ichiro, and the Olympus accounting fraud revealed by the British CEO Michael Woodford in 2011. This book will appeal to students and scholars of Japanese culture and society, anthropology, communication and media studies"--